PREVALENCE OF OBESITY IN A GROUP OF ELDERLY - Adriana, Gherbon (European Scientific Journal, ESJ, 2014)
Background&Aims: Obesity, particularly abdominal obesity, represents one of the cardiovascular risk factors. Data existing in literature, suggest that the prevalence is more than twice as high at age 55 as at age 20 and most affected are women. The purpose of this study is to asses the prevalence of obesity at elderly aged above 60 years, and association with other cardiovascular risk factors. Methods: The study group was represented by 438 elderly subjects (267 female and 171 male) aged above 60 years. Were used clinical and biochemical parameters. Results: 29% had BMI above 30 kg/m2 (33.7% F and 21.63% M, p=0.006, X2=7.38). 3.2% had BMI < 18.5 kg/m2, 34.01% had BMI between 18.5 and 24.9 kg/m2, and 33.79% BMI between 25 and 29.9 kg/m2 (55.4% F and 44.6% M, p=0.06, X2=7.38). In function of obesity grade, 71.65% had obesity grade I (65.93% F and 34.07% M, p<0.001, X2=18.48), 19.68% obesity grade II (80% F and 20% M, p<0.001, X2=18 and 8.66% obesity grade III (90.9% F and 9.1% M, p<0.001, X2=14.73). From obese and overweight subjects, 26.9% had fasting glycemia above 100 mg%, 41.45% had higher concentration of total cholesterol, 26.54% had higher concentration of triglyceride, and 66.18% had hypertension. Conclusions: At elderly we have a predominance of obesity at female. In function of obesity grade, and type we have a predominance of obesity grade I, android type. Because of association with other cardiovascular risk factors it’s imposed early measures for decreased obesity prevalence and changing lifestyle.